SWOT Analysis for Tourism Development Strategy of Samosir Regency - Toman Sony Tambunan (Universitas Airlangga, 2020)
Samosir Regency is an area that has the potential to be developed as a tourism destination through the utilization of various potential natural beauty, local wisdom, and the historical value of cultural civilization, so as to increase regional income, improve the community's economy, grow the business sector, introduce local cultural values, and contribute in developing the world of education. This study aims to analyze the strengths, weaknesses, opportunities and threats in the development of tourism in Samosir Regency as a tourist attraction. Data were collected through observation, interviews and literature study. Data analysis uses descriptive qualitative analysis. The results of the data will be used to determine the strengths, weaknesses, opportunities and threats of tourism objects in Samosir Regency. The conclusion of this study states that for the tourism development strategy of Samosir Regency, they are (1) improving the quality of facilities and infrastructure that supports tourism, (2) increasing tourism activities on a national and international scale, (3) promoting attractions on an ongoing basis to the national and international level, (4) developing various values of tourist attraction products, (5) involving the participation of the community and all interested parties in the management of attractions, and (6) improving the competency of human resources for tourism actors.